THE BEST WAYS TO IMPROVE LISTENING SKILLS IN ENGLISH - Toshbadalova , Sitora Kamoliddin qizi; Shermamatova , Zaynab Azimjanovna (Educational Research in Universal Sciences, 2023)
The creative approaches and practical techniques for enhancing English language learners’ listening comprehension are highlighted in this article. For all intermediate ELS students and English language learners, good listening in English poses challenges that point toward effective oral communication. The article’s goal is to assist students and English language learners in resolving this issue by demonstrating the outcomes of applying cutting-edge techniques and original approaches to improve English listening abilities.